AN ANALYSIS ON STUDENTS’ DIFFICULTIES IN CHANGING ACTIVE TO PASSIVE VOICE - Muhammad Hasyimsyah Batubara; Muhammad Gita Swara Mahardhika (Jurnal As-Salam, 2020)
Abstract: Today students’ are sometime less interested in understanding active and passive voice, so that when they learn it, there is a lot of incomprehension in understanding it, especially in transforming active to passive voice. This research are to know and to find out the most dominant the students’ difficulties in transforming active to passive voice form at fourth semester students’ STAIN Gajah Putih Takengon Aceh in 2017/2018 Academic Year. This study was conducted using a qualitative approach. The source of the data for this study was taken at fourth semester students’ of English Department of STAIN GP Takengon Aceh. Besides, the source of data in this research also a grammar lecturer. The technique of data collection were used observation, documentation, and interviews technique. The data analysis were used the Miles and Huberman’s models, including reduction of data, display, and conclusions; drawing/verifying. The outcomes of analysis, the researcher found the most dominant students’ difficulties in changing active to passive voice were: difficulties in determining subject, difficulties in using auxiliary verb be, and difficulties in using verb3 in passive voice and most dominant difficulties was found in form of past continuous they are not able to understand well, due to still use tools (dictionary). Based on the findings of this study, the researcher concluded that some students’ have a fairly good ability in understanding passive voice form, but some of the other students’ must also improve their understanding in English grammar. Keywords: Active and Passive Voice, Analysis, Students’ Difficulties Abstrak: Dewasa ini mahasiswa terkadang kurang tertarik untuk memahami bentuk active dan passive voice, sehingga ketika mereka mempelajarinya, ada banyak kesulitan dalam memahaminya, terutama dalam mengubah bentuk active menjadi passive. Penelitian ini untuk melihat dan mengetahui kesulitan paling dominan dalam mengubah bentuk active menjadi passive mahasiswa semester empat prodi bahasa Inggris STAIN Gajah Putih Takengon Aceh pada Tahun Akademik 2017/2018. Penelitian ini dilakukan dengan menggunakan pendekatan kualitatif. Sumber data penelitian ini diambil dari mahasiswa semester empat prodi bahasa Inggris STAIN Gajah Putih Takengon Aceh dan dosen prodi. Teknik pengumpulan data menggunakan teknik observasi, dokumentasi, dan wawancara. Analisis data menggunakan model Miles dan Huberman. Hasil analisis, peneliti menemukan kesulitan siswa yang paling dominan dalam mengubah active menjadi passive adalah: kesulitan dalam menentukan subjek, mengunakan auxiliary verb be, dan kesulitan dalam menggunakan kata kerja bentuk ke 3, dan yang paling dominan ditemukan kesulitan dalam merubah past continuous, sehingga membutuhkan alat (kamus). Berdasarkan temuan penelitian ini, peneliti menyimpulkan bahwa beberapa mahasiswa memiliki kemampuan yang cukup baik dalam memahami bentuk passive, tetapi beberapa siswa lain harus meningkatkan pemahaman mereka dalam tata bahasa Inggris. Kata Kunci: Active dan Passive Voice, Analisis, Kesulitan Siswa